2017
DOI: 10.1073/pnas.1615215114
|View full text |Cite
|
Sign up to set email alerts
|

Reelin transiently promotes N-cadherin–dependent neuronal adhesion during mouse cortical development

Abstract: Reelin is an essential glycoprotein for the establishment of the highly organized six-layered structure of neurons of the mammalian neocortex. Although the role of Reelin in the control of neuronal migration has been extensively studied at the molecular level, the mechanisms underlying Reelin-dependent neuronal layer organization are not yet fully understood. In this study, we directly showed that Reelin promotes adhesion among dissociated neocortical neurons in culture. The Reelin-mediated neuronal aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…Although Reelin controls multiple aspects of neocortical development, the mechanisms of Reelin function have not been completely understood. One of the important functions of Reelin is that it can cause neuronal aggregation both in vitro and in vivo (Hirota, Kubo, Fujino, Yamamoto, & Nakajima, 2018;Ishii et al, 2015;Kohno et al, 2015;Kubo et al, 2010;Matsunaga et al, 2017). Notably, the ectopic overexpression of Reelin in the developing neocortex causes neuronal aggregation in a birth-datedependent manner (Kubo et al, 2010), suggesting that this aggregation is a properly controlled phenomenon rather than simple aggregation.…”
mentioning
confidence: 99%
“…Although Reelin controls multiple aspects of neocortical development, the mechanisms of Reelin function have not been completely understood. One of the important functions of Reelin is that it can cause neuronal aggregation both in vitro and in vivo (Hirota, Kubo, Fujino, Yamamoto, & Nakajima, 2018;Ishii et al, 2015;Kohno et al, 2015;Kubo et al, 2010;Matsunaga et al, 2017). Notably, the ectopic overexpression of Reelin in the developing neocortex causes neuronal aggregation in a birth-datedependent manner (Kubo et al, 2010), suggesting that this aggregation is a properly controlled phenomenon rather than simple aggregation.…”
mentioning
confidence: 99%
“…Interestingly, Reelin appears to play a direct role in the increase of neuron-neuron interaction. Matsunaga et al (2017) have found that application of Reelin to dissociated cortical neurons transiently enhances neuronal adhesion. This is consistent with the finding that forced Reelin expression in migrating neurons induces neuronal aggregation (Kubo et al, 2010).…”
Section: Roles Of Neighboring Neurons During the Terminal Phase Of MImentioning
confidence: 99%
“…Although a low level of Reelin expressed in the lower IZ (Uchida et al, 2009;Hirota et al, 2015) is reported to have a different role for migrating multipolar neurons in the IZ (initiation of the multipolar-bipolar transition/control of neuron-RG cell interaction, Jossin, 2011;Jossin and Cooper, 2011;Kon et al, 2019), accumulation of these neurons in the lower IZ (Tabata et al, 2009) may also support this view. The increase of neuron-neuron interaction seems to be N-cadherindependent (Matsunaga et al, 2017). In this context, a Reelinreceptor-Dab1 pathway likely functions, because the aggregation fails to occur when binding of Reelin to the receptor is prevented by 2A-Reelin, or when Dab1 is removed from the system.…”
Section: Roles Of Neighboring Neurons During the Terminal Phase Of MImentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that Ncad has a wide range of functions in the developing nervous systems of fly and mammals (Redies et al, 1992;Redies and Takeichi, 1996;Hayashi and Carthew, 2004;Nern et al, 2008). Ncad is essential for the cortical organization of the mouse brain (Kadowaki et al, 2007;Matsunaga et al, 2017). Therefore, Ncad-dependent differential adhesion and interlayer interaction may be the essential mechanism underlying the 3D organization of column formation that is evolutionarily conserved from the fly optic lobe to mammalian brains.…”
Section: Interlayer Interactions Between the Distal And Proximal Layersmentioning
confidence: 99%